COMPARISON OF EFFICACY OF TRANEXAMIC ACID 10 MG/KG AND 15 MG/KG IN REDUCING BLEEDING AND TRANSFUSIONS IN TOTAL KNEE ARTHROPLASTY - NAMBIAR, HIMA R; S KAMATH, SHAILA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to compare the efficacy of tranexamic acid 10 mg/kg and 15 mg/kg in reducing bleeding and transfusions in total knee arthroplasty. Methods: After approval from the Institutional Ethics Committee, KMC, Mangaluru, 88 patients fulfilling the inclusion criteria of this study undergoing total knee replacements were informed of the study details and consent was obtained for the same. They were randomized into two groups using computer-generated block randomization, i.e., Group A and Group B, and were administered tranexamic acid 10 mg/kg and 15 mg/kg intravenously, respectively. Intraoperatively, hemodynamic parameters were noted. Postoperatively, hemoglobin levels were assessed on days 1 and 3. Transfusions, thromboembolic complications, and duration of hospital stay were noted. Results: Of the 88 participants of the trial, 44 in Groups A and B each, there were no significant differences in the parameters observed in this study such as intraoperative hemodynamic changes, post-operative fall in hemoglobin on day 3, number of patients requiring transfusions, number of thromboembolic events, and duration of hospital stay. A significant p-value was observed in the fall in hemoglobin in the post-operative day 3 (p=0.043). Conclusion: About 15 mg/kg tranexamic acid proved to have a lesser fall in hemoglobin on day 3 postoperatively when compared to the 10 mg/kg group. However, the fall of hemoglobin on day 3 was statistically significant and warranted a blood transfusion in two patients in the 10 mg/kg group but did not prolong their hospital stay.